2024 ELECTION LITERACY FOR BEGINNER VOTER IN AMURAN DISTRICT, SOUTH MINAHASA - Pamungkas, Sigit; Wardaningsih, Agustin Diana; Rondonuwu, Roy (Jurnal Lectura, 2025)
Freedom of expression and political participation are fundamental human rights, including the right to express political aspirations without intimidation. Ahead of the 2024 General Election, social media platforms such as TikTok, YouTube, and Instagram have become primary sources of political information for first-time voters. However, political content on these platforms is highly susceptible to hoaxes, disinformation, and hate speech. Misinformation or improper political statements can quickly go viral, potentially leading to legal consequences for the uploader. To mitigate these risks, first-time voters need political literacy to express their views ethically, accurately, and under the law. This study explores the need for political literacy among first-time voters, particularly in Amurang District, South Minahasa Regency. Using a quantitative research method, data collection was conducted through questionnaires, observations, and literature reviews. The findings of this study provide an analysis of political participation on social media and the electoral literacy needs of first-time voters.